Pengaruh Kesadaran Wajib Pajak, Sanksi Perpajakan, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak: Uji Empiris pada Wajib Pajak Kendaraan Bermotor di Kota Balikpapan - Ranita Ramadhani; Putri Kartika Yulianti; Ramli Ramli; Hendra Sanjaya Kusno (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research seeks to analyze the impact of independent variables, namely Taxpayer Awareness, Tax Penalties, and Service Quality on the dependent variable, namely Taxpayer Honesty in relation to motor vehicle tax payments. The recearch subjects were taxpayers registered at the UPTD PPRD Bapenda Balikpapan City. The research sample consisted of 400 people selected using the random sampling method with the Slovin formula for sample selection. Data collection was conducted using a questionnaire, and data analysis was performed using the Smart PLS (Partial Least Square) program. Based on the research results, Taxpayer Compliance in relation to motor vehicle tax payments is partially influenced by Taxpayer Awareness, Tax Penalties, and Service Quality. The degree of Taxpayer Complieance is positvely influenced by each of the three independent variables.